Method of Studying Λb0 Decays with One Missing Particle - Sheldon Stone; Liming Zhang (Advances in High Energy Physics)
A new technique is discussed that can be applied to Λb0 baryon decays where decays with one missing particle can be discerned from background and their branching fractions determined, along with other properties of the decays. Applications include measurements of the CKM elements |Vub| and |Vcb| and detection of any exotic objects coupling to b→s decays, such as the inflaton. Potential use of B¯0**→π+B- and B¯s0**→K+B- to investigate B- decays is also commented upon.